The Role of the Laparoscopic Autopsy Nowadays - Yaycı, Nesime Okboy (The Bulletin of Legal Medicine, 2007)
With the advent of the minimal invasive techniques in all branches of surgery, literature related with laparoscopic and thoracoscopic autopsies initiated to see following 1990, as to alternative to conventional post mortem investigation techniques. It is tried to establish the role of the minimally invasive medico legal autopsy nowadays by evaluating the studies about this new technique in this review. In cases in which the family of the deceased objects the performance of a conventional autopsy for religious or other reasons, it is very easy to take consent for laparoscopic autopsy. It’s a promising perspective, in special case groups as intoxication or nontraumatic suspicious death with the other post mortem sampling techniques. The experienced surgical performances need with minimally invasive surgical technique skill, never being an alternative to complete autopsy in traumatic cases especially for diagnosis, the condition of the surgeon probably who will perform both of the clinical intervention and the autopsy and the other causes like these are the limitations of this technique. However, this technique should be kept in mind, when the condition is available especially when the alternative is no postmortem examination at all.Key words: Laparoscopic, endoscopic, thoracoscopic, minimally invasive, autopsy
Keywords: laparoscopic; endoscopic; thoracoscopic; minimally invasive; autopsy